2013
DOI: 10.1073/pnas.1309049110
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen sulphide pathway contributes to the enhanced human platelet aggregation in hyperhomocysteinemia

Abstract: Homocysteine is metabolized to methionine by the action of 5,10methylenetetrahydrofolate reductase (MTHFR). Alternatively, by thetransulfuration pathway, homocysteine is transformed to hydrogen sulphide (H2S),through multiple steps involving cystathionine beta-synthase and cystathioninegamma-lyase. Here we have evaluated the involvement of H2S in the thromboticevents associated with hyperhomocysteinemia. To this purpose we have usedplatelets harvested from healthy volunteers or patients newly diagnosed withhyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
36
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(42 citation statements)
references
References 34 publications
2
36
0
4
Order By: Relevance
“…In contrast to the above studies, H 2 S generating salts at lower concentrations (0.1-100 μM) have been reported to enhance human platelet aggregation induced by the thrombin receptor activator peptide (TRAP-6) and to contribute to the enhanced platelet aggregation occurring during hyperhomocysteinemia (d'Emmanuele di Villa Bianca R et al 2013). A full causative mechanism was not described to explain the ability of H 2 S to enhance platelet aggregation although the arachidonic acid cascade was shown to be implicated.…”
mentioning
confidence: 83%
See 1 more Smart Citation
“…In contrast to the above studies, H 2 S generating salts at lower concentrations (0.1-100 μM) have been reported to enhance human platelet aggregation induced by the thrombin receptor activator peptide (TRAP-6) and to contribute to the enhanced platelet aggregation occurring during hyperhomocysteinemia (d'Emmanuele di Villa Bianca R et al 2013). A full causative mechanism was not described to explain the ability of H 2 S to enhance platelet aggregation although the arachidonic acid cascade was shown to be implicated.…”
mentioning
confidence: 83%
“…H 2 S is synthesised by CBS and CSE in vascular endothelial cells (Shibuya et al 2009;Whiteman et al 2011) and has been shown to act as a physiologic vasodilator and regulator of blood pressure (Yang et al 2008). Human platelets have been reported to possess both CBS and CSE by western blotting and to generate detectable amounts of H 2 S from L-cysteine (d'Emmanuele di Villa Bianca R et al 2013). In contrast, we have detected robust CBS expression by western blotting but very little or no CSE protein in human platelet lysates using three commercially available antibodies (unpublished data).…”
mentioning
confidence: 99%
“…Both CBS and CSE are expressed in platelets and generate detectable amounts of H 2 S [258]. Deficiency in H 2 S production stimulates platelets aggregation in a methionine-induced hyperhomocysteinemia rat model [259].…”
Section: Role Of Platelets In Vascular Tone Regulation: Effects Omentioning
confidence: 99%
“…Deficiency in H 2 S production stimulates platelets aggregation in a methionine-induced hyperhomocysteinemia rat model [259]. H 2 S inhibits platelet activity both in vivo and in vitro [259266], although controversial [258]. …”
Section: Role Of Platelets In Vascular Tone Regulation: Effects Omentioning
confidence: 99%
See 1 more Smart Citation